1980
DOI: 10.1056/nejm198002283020903
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Control in Parents of Victims of Sudden-Infant-Death Syndrome

Abstract: Since a defective ventilatory-control mechanism may have a role in the sudden-infant-death syndrome (SIDS), and hereditary factors influence the degree of ventilatory drive, we measured ventilatory responsiveness to carbon dioxide with and without increased airway resistance in 12 parents of SIDS victims and 12 control parents matched for age and size. Ventilatory response (delta VI/delta PCO2) and "respiratory drive" (delta P100/delta PCO2) were measured both with and without added resistance to inspiratory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The lack of any effect of naloxone on periodic breathing and prolonged apnoeas in infants is in agreement with the results of Schiffman et al [11], who investigated the effect of naloxone on impaired ventilatory control mechanisms in parents of SIDS-victims.…”
Section: Discussionsupporting
confidence: 91%
“…The lack of any effect of naloxone on periodic breathing and prolonged apnoeas in infants is in agreement with the results of Schiffman et al [11], who investigated the effect of naloxone on impaired ventilatory control mechanisms in parents of SIDS-victims.…”
Section: Discussionsupporting
confidence: 91%
“…Redline et al 91 showed that ventilatory responsiveness to hypoxia and hypercapnia was depressed in family members of OSA patients. In addition, a depressed response to hypoxia has been recorded in the siblings of infants with SIDS92 and also in the parents of SIDS victims 93…”
Section: Familial Osa Syndromementioning
confidence: 99%
“…Over 100 hypotheses have been formulated and investigated. Some important areas of current research include studies related to prolonged sleep, apnea, chronic oxygen deficiency, and enzyme abnormalities (15,16).…”
Section: Discussionmentioning
confidence: 99%